Insurance against risk? Economic cost and compensation of job loss in different welfare states - Bedük Selçuk; Fasang Anette Eva; Harkness Susan; Bastholm Andrade Stefan; Büyükkeçeci Zafer; Karhula Aleksi; Helske Satu (SocArXiv, 2025)
In this paper, we examine the cost of job loss to household incomes, and the extent to which initial losses is compensated through the market, within the household and by the social security programmes. We use high quality survey and admin data from Denmark, Finland, Germany and the UK for the period of 1990-2018 and monitor incomes after job loss using an event study design. Our findings reveal significant, relatively persistent and long-term penalties on household incomes (around 9-13% of previous earnings) that are only higher in the UK in the short-term. Market appears to be the primary mechanism of compensation in all countries, while the relative importance of household and state compensations vary across countries. State compensation plays a crucial role in mitigating immediate income losses, while market compensation becomes more important over time. Household compensation mainly acts as a substitute for market and state compensation.